A study on the issues of clinical waste management (case study: General Hospital in District of Perak) / Nur Shafiqa Anuwa and Nurulanis Ahmad@Mohamed - Anuwa, Nur Shafiqa; Ahmad@Mohamed, Nurulanis (2019)
Clinical Waste Management (CWM) became a debate in worldwide especially in developed countries as well as low-income countries due to the rapid urbanization and population growth. Malaysia is no exception from facing the issues as the amount of clinical waste continues increasing by 31% with 22 thousand tons in 2014 and the following years. This country ranked the second highest country in Asia that generates the most of clinical waste as the effect of not uniform in managing the waste. Consequently, unmanageable clinical waste is hazardous towards human health and environmental due to the contagious nature of waste that has the potential to produce disease through the dissemination of pathogens. Therefore, the objectives of this paper are to identify and determine the issues arise of clinical waste management at general hospitals in districts of Perak. The primary data is collected by using questionnaire which is the result of the questionnaire will be evaluate with SPSS and interview to verify the result. The findings resulted in lack of awareness and knowledge of the management employees the main issues faced by general hospital in district of Perak followed by the issues on the policies of CWM.